2019
DOI: 10.12968/bjon.2019.28.10.s4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and personal resilience in the first two years after breast cancer diagnosis: systematic integrative review

Abstract: The aim of this systematic integrative review was to examine the early impacts of a breast cancer diagnosis (up to 2 years after diagnosis) in relation to quality of life and personal resilience. The bibliographic databases of Medline, CINAHL, Cochrane, and Psychology and Behavioral Science Collection were searched using predetermined search criteria. Research studies published up to February 2019 were considered and following appraisal 36 articles were included in the review. Younger age, disease progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 55 publications
4
17
0
1
Order By: Relevance
“…The emotional, social/family, and physical well-being subscales were also affected negatively during the disease course. The ndings were consistent with prior research [7,18] that indicated breast cancer patients had di culties with physical, psychological, and social functioning.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The emotional, social/family, and physical well-being subscales were also affected negatively during the disease course. The ndings were consistent with prior research [7,18] that indicated breast cancer patients had di culties with physical, psychological, and social functioning.…”
Section: Discussionsupporting
confidence: 89%
“…This ability changes continuously with the interactions between the individual and the environment [4][5][6]. Resilience levels integrate physiological, psychological, and social functions that affect an individual's HRQoL after suffering from stressful events [7]. Women with breast cancer experience different degrees of psychological trauma during the process of diagnosis, treatment, and rehabilitation [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases and various negative stressors affect the HRQoL of breast cancer patients with varying degrees, especially in the eld of psychosocial functioning [4]. Commonly reported factors that in uence HRQoL include anxiety, depression, and despair [5,6]; resilience [7]; perceived social support (PSS) [8,9]; and coping style (CS) [10]. CS is also an important mediator variable of HRQoL [11].…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes estudios han apreciado como determinadas estrategias de afrontamiento (EA) se vinculan a mejor calidad de vida y resultan más adaptativas, mientras que otras estrategias se relacionan con un peor ajuste psicosocial y síntomas depresivos mayores (Edward, Chipman, Giandinoto, & Robinson, 2019;Paek et al, 2016). Según la teoría transaccional el afrontamiento no es estático, sino que cambia con el tiempo (Lazarus & Folkman, 1984).…”
Section: Introductionunclassified